2009
DOI: 10.1103/physreve.80.060303
|View full text |Cite
|
Sign up to set email alerts
|

Stress correlations in granular materials: An entropic formulation

Abstract: We study the response of dry granular materials to external stress using experiment, simulation, and theory. We derive a Ginzburg-Landau functional that enforces mechanical stability and positivity of contact forces. In this framework, the elastic moduli depend only on the applied stress. A combination of this feature and the positivity constraint leads to stress correlations whose shape and magnitude are extremely sensitive to the nature of the applied stress. The predictions from the theory describe the stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
31
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 23 publications
5
31
0
Order By: Relevance
“…A field theoretical model [47] of the spatial stress fluctuations was developed based on numerical data for frictionless disks, and this has been used to predict the stress fluctuations of numerical and experimental packings under pure shear [57].…”
Section: Microcanonical and Canonical Formulationsmentioning
confidence: 99%
“…A field theoretical model [47] of the spatial stress fluctuations was developed based on numerical data for frictionless disks, and this has been used to predict the stress fluctuations of numerical and experimental packings under pure shear [57].…”
Section: Microcanonical and Canonical Formulationsmentioning
confidence: 99%
“…One of the most promising recent approaches, proposed by Henkes and Chakraborty, is based on a statistical ensemble which equally weights all continuum stress fields which satisfy force balance and positivity constraints [18]. Previous work within this framework focused on pressure-pressure correlations where no interesting lengthscale was detected (in the isotropically prepared state) in either experiments or simulations [4].…”
Section: Model and Protocolmentioning
confidence: 99%
“…figure 1 below), quantitative characterizations of them have only recently been reported. These recent approaches have focused on topological characterizations [3], 2-point correlations in the local hydrostatic pressure [4], and statistics of spatially averaged forces [5]. These works showed that there are some characteristics in the spatial structure of the stress field which are independent of density, but they left open the important question of whether one can define a characteristic lengthscale associated with the general visual impression one gets when observing the contact force network.…”
mentioning
confidence: 99%
“…The relative fluctuations χ P ≡ N σ 2 (P/ P B ), can be non-zero, and a diverging χ P would then imply a diverging χ Λ . Because of the bounded nature of P [23][24][25], however, χ P can only diverge at the unjamming transition where P B → 0 (see Methods). We find that χ P does diverge ( Fig.…”
mentioning
confidence: 99%